Evolving Weak Form Market Efficiency in BRICS+ Markets - Rifka Indi; Danes Quirira Octavio; Adhi Widyakto (Transpublika Publisher, 2026)
The Efficient Market Hypothesis (EMH), particularly in its weak form, remains a subject of debate, especially in emerging and developing markets where structural, institutional, and behavioral factors may hinder informational efficiency. The recent enlargement of the BRICS group to BRICS+ now includes a wider range of diverse economies. Therefore, a thorough reexamination of weak‑form market efficiency across these markets is required. This study explores weak‑form efficiency in BRICS+ stock markets and determines if stock returns follow a random walk or display predictable trends over time. This study analyzes daily returns of nine stock indexes including Brazilian, Russian, Indian, Chinese, South African, Saudi Arabia, Egyptian, and United Arab Emirates, and Indonesian between January 2006 and December 2024. We employed run tests, unit root tests (Augmented Dickey-Fuller and Phillips-Perron), and variance ratio tests to determine the randomness and predictability of returns. Conflicting evidence emerges from the empirical analysis of weak‑form efficiency. On one hand, randomness is supported by both run tests and unit root tests for every BRICS+ index. On the other hand, variance ratio tests produce significant results that contradict the random walk hypothesis. Such opposing findings indicate that BRICS+ stock markets are not consistently weak‑form efficient. They instead confirm the Adaptive Market Hypothesis, a framework that is only partially applicable and varies with context. This hypothesis is influenced by evolving economic circumstances, the maturity of institutions, and the actions of investors. It highlights the need to adopt adaptive investment strategy and flexible regulation strategies in dynamic market environments.